Faktor yang Berhubungan dengan Kejadian Demam Berdarah Dengue (DBD) di Daerah Endemis Tinggi Kota Semarang - Zulfa, Afifah Afanin; Martini, Martini; Udijono, Ari; Hestiningsih, Retno; Jayanti, Siswi (Jurnal Riset Kesehatan Masyarakat, 2021)
Abstrak:  Dengue hemorrhagic fever is a mosquito-borne transmitted disease which prevention is through 1 Jumantik 1 Home movement (1J1HM). 1J1HM is a program which included the activity of preventing Dengue Hemorrhagic Fever (DHF), called Mosquito Nest Eradication (PSN 3M Plus). The purpose of this study is to describe the actions in the implementation of 1J1HM and to find the factors correlate with the numbers of DHF case in the Sendangmulyo Village. The type of the research is descriptive observational, quantitative data with a cross-sectional approach. With 100 residents of Sendangmulyo Village as the sample,  using the sampling methode of purposive sampling. Data analysis used is chi-square test. The result shows that the number of respondents implementing 1J1HM in Sendangmulyo Village is only 35%. The result means not half of the samples are implementing the action of 1J1HM.  Bivariate analysis showed that there are correlations between the level of knowledge (p=0.012) POR 3.9 (CI 1.29-11.9) and attitude (p=0.000) POR 16.5 (CI 6.38-42.6) with the actions in 1J1HM in Kelurahan Sendangmulyo. And there are no correlations between age and education level with the action of 1J1HM. It is hoped that residents in Sendangmulyo village would be have better environmental hygiene and health, better understanding and increased in information.